Active and passive magnetic shielding for use in OPM-MEG - Edwards, Lucy J (2024)
Magnetic shielding is an essential part of many sensitive experiments including magnetoencephalography (MEG) systems that measure tiny magnetic fields generated by the simultaneous firing of neurons in the brain. Recent advances in MEG have arisen due to the use of head mounted optically pumped magnetometers (OPMs). MEG scans must be carried out inside magnetically shielded rooms (MSRs). Passive shields made up of several layers of ferromagnetic material, combined with active shielding using electromagnetic coils, create very low magnetic field environments which enable OPMs to detect femtotesla brain fields. In order to open up the scanning environment, and increase the range of patient movement, the coils must be mounted on the walls of the MSR. However, as the coils move closer to the ferromagnetic walls, magnetic field interactions between the two occur. Therefore it is important to understand how the coils will interact with the shielding material in order to design effective shielding systems. This thesis explores interactions between electromagnetic coils and the ferromagnetic walls of a magnetic shield by comparing experimental measurements of magnetic fields produced by a small circular coil mounted onto the inside face of a single layer, 55 × 55 × 55 cm3 MuMetal box, to a mathematical model describing the interaction of a planar coil close to an infinite plane with high magnetic permeability. Furthermore, this thesis investigates how the shielding factor of a magnetic shield can be enhanced using a technique called ‘shaking’. Tests were carried out on a three layer MuMetal magnetic shield made up of nested cylinders, which showed that the shielding factor for low frequency magnetic fields could be improved by applying alternating currents to coils wound around the MuMetal during an experiment. This could be a potential solution to improving the shielding factors of lighter magnetically shielded rooms used for OPM-MEG. Finally, this thesis explores a new method to enable the nulled volume produced by a coil system to move with a sensor during an experiment, by continuously driving the nulling coils surrounding the sensor with unique frequencies. Experiments were carried out using a fluxgate magnetometer inside the 55 × 55 × 55 cm3 MuMetal box. The methods used to carry out the continuous calibration and field cancellation are outlined and a custom LabVIEW program, which was developed to control the magnetic field during experiments, is described. Experiments showed that the magnetic field at the fluxgate magnetometer could be nulled during both translations and rotations. Improving the shielding factor of magnetically shielded rooms, and also understanding how passive and active magnetic shielding techniques interact, is important as we move towards producing lighter magnetic shields which will rely more on active shielding to operate at efficiencies equivalent to their multi-layer counterparts. Furthermore, development of lighter magnetic shields will help enable OPM-MEG to become an affordable and widely used brain imaging technique.